THE SOCIAL STATUS AND CULTURAL IDENTIFICATION OF LABOR MIGRANTS (A CASE STUDY OF UZBEKS IN SOUTH KOREA) - Rahimberdiyev Sardorbek Bekmurod ugli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT This article examines the socio-economic conditions and cultural identification of Uzbek labor migrants in the Republic of Korea. The study relies exclusively on empirical  field  materials,  interviews,  and  analytical  observations  included  in  the dissertation dataset. The article analyzes the structural dynamics of migration flows, demographic composition, integration into the labor market, social conditions, and the mechanisms  for  preserving  cultural  identity  within  Uzbek  migrant  communities. Particular attention is paid to the role of diaspora institutions, religious practices, and symbolic cultural elements in shaping collective identity. The findings indicate that Uzbek migrants demonstrate a dual identification model, whereby, alongside economic integration, they maintain their national-cultural identity through social cohesion and cultural reproduction.